1993
DOI: 10.1111/j.1468-0424.1993.tb00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and National Identity in fin de siècle Greece

Abstract: Greece ELENI VARIKASFor my grandmother, the refugee school teacher from Asia Minor, who taught me how not to hate the 'enemy'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to Foucault (1978), family serves in the (re)production of patriarchal 439 structures and conventional gender roles. This is also the case in Greece where traditional family 440 structures and gender relations persist and Greek women find it hard to escape from their webs of 441 power (Kyriazis, 1998;Lazaridis, 1994;Varikas, 1993). The institution of the family plays a 442 significant role in maintaining traditional roles and values, because it is within family that girlsleadership and protect/support his family.…”
Section: Participants 311mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Foucault (1978), family serves in the (re)production of patriarchal 439 structures and conventional gender roles. This is also the case in Greece where traditional family 440 structures and gender relations persist and Greek women find it hard to escape from their webs of 441 power (Kyriazis, 1998;Lazaridis, 1994;Varikas, 1993). The institution of the family plays a 442 significant role in maintaining traditional roles and values, because it is within family that girlsleadership and protect/support his family.…”
Section: Participants 311mentioning
confidence: 99%
“…Examining the Greek national identity, Varikas (1993) household and protected by male relatives, Greek women appear to develop a sense of both 228 safety (Athanasiadis, 2007) and innocence, since excluded from power, they are not responsible 229…”
Section: Positioning the Female Judoka In Greek Culture 200mentioning
confidence: 99%
“…Research has shown many instances of women teachers' patriotic activities. As it has been commented (Varikas, 1987(Varikas, , 1993, the need and strong wish of those women to become independent and escape a meaningless and idle life was combined with their patriotic activities, patriotic exaltation on the one hand and attraction for travelling and adventure on the other. Therefore, the enlivenment of the Great Idea, the idea of the expansion of the Greek state and the reappropriation of its past glory, opened women teachers a path for political involvement and was used by them as a vehicle to claim the right of citizenship [29].…”
Section: Heterotopias Of Self Writingmentioning
confidence: 99%